2017
DOI: 10.3389/fimmu.2017.01249
|View full text |Cite
|
Sign up to set email alerts
|

Specific Pathogen Recognition by Multiple Innate Immune Sensors in an Invertebrate

Abstract: Detection of pathogens by all living organisms is the primary step needed to implement a coherent and efficient immune response. This implies a mediation by different soluble and/or membrane-anchored proteins related to innate immune receptors called PRRs (pattern-recognition receptors) to trigger immune signaling pathways. In most invertebrates, their roles have been inferred by analogy to those already characterized in vertebrate homologs. Despite the induction of their gene expression upon challenge and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 60 publications
(84 reference statements)
3
49
0
Order By: Relevance
“…Biomphalysin forms a complex with humoral immune molecules (FREP, TEP) [45]. Altogether, this suggests that Biomphalysin is involved in pathogen clearance [27].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Biomphalysin forms a complex with humoral immune molecules (FREP, TEP) [45]. Altogether, this suggests that Biomphalysin is involved in pathogen clearance [27].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it can be expected that snails have to co-evolve with these pathogen communities and should possess sophisticated immune processes to cope with them. In the past decade, the molecular basis of the B. glabrata innate immune response has been investigated at the genomic [14][15][16][17], transcriptomic [18][19][20], proteomic/biochemical [21][22][23][24][25][26][27] and epigenomic levels [28][29][30][31][32]. These studies have revealed that various molecules and pathways involved in immune recognition, immune regulation/activation and immune effector systems participate in a complex interplay between host and pathogen to maintain the homeostasis of the organism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type I interferons (IFNs), the crucial antiviral cytokines, activate intracellular antimicrobial programs and influence the development of innate and adaptive immune responses (Ivashkiv and Donlin, 2014). During virus infection, the pattern-recognition receptors (PRRs) recognize specific pathogen-associated molecular patterns (PAMPs) to regulate the expression of IFNs through intracellular signaling cascades (Takeuchi and Akira, 2007;Tetreau et al, 2017). In these signaling pathways, NF-κB essential modulator (NEMO) and virus-induced signaling adapter (VISA, also called MAVS or IPS-1) play essential roles in regulating the expression of IFN-I and inflammatory cytokines (Kawai et al, 2005;Satoshi and Shizuo, 2006;Akira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%